Optical coherence tomography measures correlate with brain and spinal cord atrophy and multiple sclerosis disease‐related disability. (28th July 2020) - Vidal‐Jordana, A.; Pareto, D.; Cabello, S.; Alberich, M.; Rio, J.; Tintore, M.; Auger, C.; Montalban, X.; Rovira, A.; Sastre‐Garriga, J.
Abstract : Background and purpose: Both optical coherence tomography (OCT) and magnetic resonance imaging (MRI) volumetric measures have been postulated as potential biomarkers of multiple sclerosis (MS)‐related disability. The aim of the study was to investigate the association between OCT and brain volume and spinal cord area (SCA) parameters in patients with relapsing MS and to assess their independent associations with disability. Methods: This was a cross‐sectional analysis of 90 patients with MS who underwent OCT and MRI examination. Values of peripapillary retinal nerve fibre layer (pRNFL), ganglion cell/inner plexiform layer (GCIPL) and inner nuclear layer of eyes without previous optic neuritis were obtained. SCA and brain parenchymal fraction (BPF), grey and white matter fractions were obtained. Multivariable regression analyses were conducted with disability as dependent variable. Results: Lower pRNFL thickness and lower GCIPL volume as well as lower BPF, grey matter fraction and SCA were associated with a longer disease duration and a higher Expanded Disability Status Scale score. Lower pRNFL thickness and GCIPL volumes were associated with lower BPF and SCA. In the multivariable logistic regression analyses, pRNFL thickness and GCIPL volume outperformed MRI in predicting disability. Conclusions: The OCT measures correlate with brain and spinal cord atrophy and appear more closely associated with disability than MRI volumetric measures.